1989
DOI: 10.1017/s0899367x00002014
|View full text |Cite
|
Sign up to set email alerts
|

Off-Farm Employment Decisions by Massachusetts Farm Households

Abstract: The off-farm labor participation and supply decisions of Massachusetts farm families were estimated in a model which allows for joint decisions. The hypothesis of joint off-farm participation decisions by operators and spouses was rejected. However, there was some evidence that the hours supplied by the farm operator was dependent upon the decision by the spouse to work off-farm. Farm operators were found to respond to both family and farm characteristics in making participation and supply decisions. Spouses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 9 publications
1
23
2
Order By: Relevance
“…The correlation coefficient's lack of significance is consistent with other joint participation decision studies (Huffman and Lange;Lass, Findeis, and Hallberg 1989). Estimated cross-equation correlation was positive, 0.15, but not significantly different from zero (calculated t-statistic was 1.50).…”
Section: Participation Modelssupporting
confidence: 85%
“…The correlation coefficient's lack of significance is consistent with other joint participation decision studies (Huffman and Lange;Lass, Findeis, and Hallberg 1989). Estimated cross-equation correlation was positive, 0.15, but not significantly different from zero (calculated t-statistic was 1.50).…”
Section: Participation Modelssupporting
confidence: 85%
“…A 1999 study by Korb shows that younger, better-educated farmers and spouses are most likely to work off farm. In that the operator's age and education are both factors that are associated with offfarm employment have been empirically tested and supported in a number of studies (e.g., see Huffman, 1980;Huffman and Lange;Gould and Saupe;Lass, Findeis, and Hallberg;Gunter and McNamara;Lass and Gempesaw;Huffman and El-Osta;Corsi and Findeis;among others).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education has a similar ambiguous effect on off-farm employment as age in that it is hypothesized to increase both farm labor productivity and the offfarm wage rate. However, previous studies have often found that an increase in the level of education increases the probability of working off the farm (Sumner 1982;Lass et al 1989;Gunter and McNamara 1990). As with age, education is measured by categorical variables according to the highest level of education attained: elementary school (EDELEM), some high school (EDSHS), completed high school (EDCHS), some college (EDSCLG), and at least a college diploma or university degree (EDUD).…”
Section: Canadian Journal Of Agricultural Economicsmentioning
confidence: 99%
“…Farm characteristics, K , will influence the value of on-farm labor productivity. Previous studies note the impact of different farming systems on the decision to work off the farm (Sumner 1982;Lass et al 1989;Gould and Saupe 1989). The reason for such a specification is that farming systems that demand extensive labor requirements will be less likely to have operators involved in off-farm employment.…”
Section: Canadian Journal Of Agricultural Economicsmentioning
confidence: 99%